Pembinaan Terhadap Anak Didik Pemasyarakatan Di LembagaPembinaan Khusus Anak (LPKA) DalamMewujudkan Tujuan Pemidanaan(Studi Kasus di Lembaga Pembinaan Khusus Anak (LPKA)Kelas I Kutoarjo-Purworejo) - Wibisono, Rano Sandy, Muchamat Iksan, S.H., M.H, Bambang Sukoco S.H.,M.H (2016)
This study aims to determine the formation, development and results of the obstacles often encountered Special Children's Development Institute (LPKA) Class I Kutoarjo-Purworejo in fostering correctional protégé. This research method using juridical empirical data sources consist of primary data, data from the study, and secondary data from a source of primary law, secondary and tertiary. Data were collected by literature study and interviews. Analysis of data using qualitative analysis. The results showed that the students correctional supervision on a way to implement a coaching program that includes personality development and fostering of independence (entrepreneurship) under Article 3 of Government Regulation No. 31 of 1999 on Development and Mentoring Citizens Patronage of Corrections. The results of coaching proved to have succeeded in realizing the objective of sentencing is qualitatively namely to prevent a resurgence of crime and the quantitative calculation of the percentage of students who become recidivists Corrections within 12 (twelve) months, only 11.1%. While the obstacles encountered is the lack of infrastructure and human resources.